Analisis Pengendalian Persediaan dengan Metode Economic Order Quantity (EOQ) Kelompok Tani - Dwiputrianti, Septiana; Aprilia, Zahra Asri; Fitriani, F Laksmi; Rejeki, Putri Wulandari Atur (Suluh Pembangunan : Journal of Extension and Development, 2025)
The research addresses significant issues in inventory management, such as overstock and understock, which have posed challenges to the group’s operations. The study aims to identify the most effective inventory management method that can minimize costs while ensuring consistent availability of raw materials. Utilizing the EOQ method, the study provides a systematic approach to determining the optimal order quantity and reorder point, ensuring that the group can meet production demands without incurring unnecessary holding or ordering costs. The research employs a qualitative approach, focusing on data collection through interviews and documentation from key members of Farmer Group X. The findings indicate that the current inventory practices were inefficient, leading to either surplus stock or material shortages. By implementing EOQ, the group can significantly reduce total inventory costs and improve their production scheduling. This study is crucial in the field of public administration and management as it provides practical recommendations for optimizing inventory control in agricultural groups. The results contribute to both theoretical frameworks on inventory management and offer practical solutions that can be adopted by similar agricultural organizations. The findings will help in developing sustainable management practices that align with the group's goals of improving product quality, reducing costs, and ensuring long-term operational efficiency.